2020
DOI: 10.1002/ppul.25124
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of EBUS‐TBNA and EUS‐B‐FNA in children: A systematic review and meta‐analysis

Abstract: Background Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) and transesophageal bronchoscopic ultrasound‐guided fine‐needle aspiration (EUS‐B‐FNA) are established modalities for evaluation of mediastinal/hilar lymphadenopathy in adults. Limited literature is available on the utility of these modalities in the pediatric population. Herein, we perform a systematic review and meta‐analysis on the yield and safety of EBUS‐TBNA and EUS‐B‐FNA in children. Methods We performed a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
(84 reference statements)
2
13
0
Order By: Relevance
“…EBUS-guided TBNA is an established diagnostic tool in adults, but still infrequently applied in pediatric respiratory medicine due to the requirement of a large-diameter bronchoscope. Our single-center experience in 45 consecutive subjects, the largest case series reported to date, expands current evidence on the procedure's efficacy and safety as recently reviewed by Madan et al 2 Our use of EBUS and lymph node biopsy almost tripled the bacteriological confirmation rate in comparison to sputum-or gastric aspirate-based testing alone. Bronchoscopic BAL only increased the confirmation rate by a factor of 1.3 relative to standard testing, and additional TBNA resulted in a further doubling of the diagnostic yield.…”
Section: To the Editorsupporting
confidence: 74%
“…EBUS-guided TBNA is an established diagnostic tool in adults, but still infrequently applied in pediatric respiratory medicine due to the requirement of a large-diameter bronchoscope. Our single-center experience in 45 consecutive subjects, the largest case series reported to date, expands current evidence on the procedure's efficacy and safety as recently reviewed by Madan et al 2 Our use of EBUS and lymph node biopsy almost tripled the bacteriological confirmation rate in comparison to sputum-or gastric aspirate-based testing alone. Bronchoscopic BAL only increased the confirmation rate by a factor of 1.3 relative to standard testing, and additional TBNA resulted in a further doubling of the diagnostic yield.…”
Section: To the Editorsupporting
confidence: 74%
“…The diagnostic yield is acceptable and may avoid the need for invasive biopsy procedures in majority. [ 2 4 9 10 11 12 13 14 ] EUS-B-FNA may be performed in children even 3 years and younger for sampling the esophageal accessible lymph nodes. [ 15 ] However, one needs to highlight that performing EBUS-TBNA and EUS-B-FNA in children requires reasonable expertise and experience with EBUS-TBNA.…”
Section: Discussionmentioning
confidence: 99%
“…Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a standard of care modality for evaluating mediastinal lymphadenopathy and mediastinal lesions in adults and children. [ 1 2 3 4 ] Ever since EBUS-TBNA was introduced into the realm of clinical pulmonology in 2003, it has revolutionized the approach towards evaluating mediastinal lymphadenopathy and other mediastinal lesions. [ 5 ] However, like flexible bronchoscopy, there is variability in the performance technique in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…Madan concluded that EBUS-TBNA and EBUS-B-FNA is safe in children with mediastinal lymphadenopathy; it may be considered as the first-line diagnostic modality. 50 Radial probe EBUS employs a flexible catheter housing a rotating ultrasound transducer, which produces a 360-degree ('radial') ultrasound image and was first used to guide TBLB by Herth et al 51 These radial probes are compatible with channel diameters from 2.0 mm to 2.8 mm. They can be inserted directly through the working channel or used with a guide sheath.…”
Section: Transbronchial Needle Aspirationmentioning
confidence: 99%